Some of them with aspects of training students in surveyors student-centered individual training - KOCHERYGIN, Leonid (Journal of Education, Technology and Computer Science, 2013)
The article discusses some problems with the training of students, future land surveyors, and creates educational opportunities for the development of their autonomy, community and accountability through student-oriented structure individualized studying